Investigating the Students Anxiety in Learning English as Foreign Language at VIII Grade in SMP Negeri 9 Pematangsiantar - Pane, Debora Ombun Natio S.; Hutauruk, Bertaria Sohnata; Silalahi, Dumaris E. (Journal Corner of Education, Linguistics, and Literature, 2025)
Foreign Language Anxiety (FLA) encompasses feelings of fear, nervousness, and negative self-perceptions that can impede learners’ progress in acquiring a new language. Within the Indonesian educational landscape, where English is introduced as a foreign language, such anxiety presents a formidable obstacle to achieving language proficiency. This research explored the various types and intensities of foreign language anxiety experienced by eighth-grade students at SMP Negeri 9 Pematangsiantar in their English learning journey. Employing descriptive qualitative approach, this research gathered data through surveys administered to eighth-grade students, complemented by classroom observations and open-ended student responses. The findings indicated that anxiety levels are most pronounced during speaking activities and examinations, primarily driven by limited vocabulary, apprehension about making mistakes, and classroom environment factors. The predominant manifestations of anxiety included communication apprehension and fear of negative evaluation, with many students expressing feelings of embarrassment and reluctance to actively participate. To cope, students resorted to strategies such as self-research, note-taking, and seeking help from peers; however, these methods tended to be simple and unstructured, limiting their effectiveness. The research underscored teachers’ role played in cultivating a supportive, non-threatening classroom atmosphere where students feel safe to practice English without fear of judgment. Ultimately, this research enriched understanding of foreign language anxiety within Indonesian educational context and provides valuable insights for teachers aiming to implement strategies that reduce anxiety and foster greater confidence among students in English learning.